IMPACT OF REVOLUTIONARY ARTIFICIAL INTELLIGENCE BASED CODE AUTOMATION MODELS ON SOFTWARE DEVELOPMENT INDUSTRY AND SOFTWARE DEVELOPERS - Jain, Varsha (Digital Repository of Theses, 2023)
The purpose of this study is to explore the impact of large language models on the software industry. The study seeks to answer the research question, “How does automating software development impact the job of software professionals and how much effort and cost-saving will organizations get by augmenting software development with artificial intelligence”. The goal is to analyze the various software development tasks that can be automated using artificial intelligence-based code automation models and study the impact of this automation on software professionals and the industry.